Genetic Immunization with CDR3-Based Fusion Vaccine Confers Protection and Long-Term Tumor-Free Survival in a Mouse Model of Lymphoma. (27th April 2010) - Iurescia, Sandra; Fioretti, Daniela; Pierimarchi, Pasquale; Signori, Emanuela; Zonfrillo, Manuela; Tonon, Giancarlo; Fazio, Vito M.; Rinaldi, Monica
Abstract : Therapeutic vaccination against idiotype is a promising strategy for immunotherapy of B-cell malignancies. We have previously shown that CDR3-based DNA immunization can induce immune response against lymphoma and explored this strategy to provide protection in a murine B-cell lymphoma model. Here we performed vaccination employing as immunogen a naked DNA fusion product. The DNA vaccine was generated following fusion of a sequence derived from tetanus toxin fragment C to the V H CDR 3 109 − 116 epitope. Induction of tumor-specific immunity as well as ability to inhibit growth of the aggressive 38C13 lymphoma and to prolong survival of vaccinated mice has been tested. We determined that DNA fusion vaccine induced immune response, elicited a strong protective antitumor immunity, and ensured almost complete long-term tumor-free survival of vaccinated mice. Our results show that CDR3-based DNA fusion vaccines hold promise for vaccination against lymphoma.